Migration in rural Burkina Faso - Wouterse, Fleur Stephanie (Cornell University, 2007)
Migration plays an important role in development and as a strategy for poverty reduction. A recent World Bank investigation finds a significant positive relationship between international migration and poverty reduction at the country level (Adams and Page 2003). Burkina Faso, whose conditions for agriculture are far from favorable, has a long history of migratory movement, and migration within West Africa has long taken place in response to drought and low agricultural productivity. In recent decades, migration to destinations outside the African continent and in particular to Western Europe has become more important for migrants from Burkina Faso. Migration can be considered a livelihood diversification strategy because remittances resulting from migration constitute an income source that is uncorrelated with household income from agriculture. Migration affects the sending household in three ways. First, when a household member migrates, the household loses labor. Second, migration often results in remittances. Third, migration implies a reduction in household size for consumption. It is likely that both motives for and consequences of migration will differ by whether the destination is within Africa or outside Africa. Migration to destinations outside Africa is expensive in terms of transport costs but generates a comparatively high level of remittances for the household. This case study discusses the determinants and consequences of migration for households in four villages situated on the Central Plateau of Burkina Faso. Two forms of migration are distinguished: migration within Africa (continental migration) and migration to a destination outside Africa (intercontinental migration). A critical question is what happens to the welfare of rural households when they engage in either form of migration. When households lose labor, it may be harder for them to participate in and generate income from other activities such as agriculture. Remittances may partly compensate for these negative effects. In addition, a reduction in household size means less consumption pressure on the household. Considering the welfare impacts of both forms of migration and the wider policy environment, your assignment is to consider how policy could be directed toward enhancing the role of migration in local development.